4(x-6)+6=6(x-2)-4

Simple and best practice solution for 4(x-6)+6=6(x-2)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-6)+6=6(x-2)-4 equation:


Simplifying
4(x + -6) + 6 = 6(x + -2) + -4

Reorder the terms:
4(-6 + x) + 6 = 6(x + -2) + -4
(-6 * 4 + x * 4) + 6 = 6(x + -2) + -4
(-24 + 4x) + 6 = 6(x + -2) + -4

Reorder the terms:
-24 + 6 + 4x = 6(x + -2) + -4

Combine like terms: -24 + 6 = -18
-18 + 4x = 6(x + -2) + -4

Reorder the terms:
-18 + 4x = 6(-2 + x) + -4
-18 + 4x = (-2 * 6 + x * 6) + -4
-18 + 4x = (-12 + 6x) + -4

Reorder the terms:
-18 + 4x = -12 + -4 + 6x

Combine like terms: -12 + -4 = -16
-18 + 4x = -16 + 6x

Solving
-18 + 4x = -16 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-18 + 4x + -6x = -16 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-18 + -2x = -16 + 6x + -6x

Combine like terms: 6x + -6x = 0
-18 + -2x = -16 + 0
-18 + -2x = -16

Add '18' to each side of the equation.
-18 + 18 + -2x = -16 + 18

Combine like terms: -18 + 18 = 0
0 + -2x = -16 + 18
-2x = -16 + 18

Combine like terms: -16 + 18 = 2
-2x = 2

Divide each side by '-2'.
x = -1

Simplifying
x = -1

See similar equations:

| 11-h=-10-7h | | -10x+3=0 | | 52-25-3=x+7 | | 8c-4=5c+10 | | 7-2(3x-5)=2+3(4x-7) | | 8(x+5)=6(x-2) | | 26x-6-17x+3=19x-4-10x+16 | | x+5-1=26-14 | | x^2+2=23 | | (11-2x)(6-2x)(x)=40 | | .04(x)+.08(x)=10000 | | x+(.07*x)=100 | | 4v^2+24v-64= | | .04(x)+.08(x)=-124 | | 6x+13-8x=16-15x+13x-3 | | -1/3y=-9 | | 50g-7=44g+35 | | x-4=2(3x-1) | | 12x=11x-14x | | x+(.07*x)=50 | | 2(3+2x)-3=27 | | .02(.8x)+.05x=119.6 | | sqrt(x-1)+x=7 | | 2.5+.075p=.01p | | 5ln(2x-2)+10=0 | | X^2+13x-31=7x-4 | | 20x+10=5*20 | | 2.1x-8.1=3.16-5.4x | | 2p^2/5-p^1/5-1=0 | | H(t)=-10t^2+10t+24 | | .05x+.06(3x)=943 | | 5y-3+y+29=5y+30-1y |

Equations solver categories